Inclisiran inhibits oxidized low-density lipoprotein-induced foam cell formation in Raw264.7 macrophages via activating the PPARγ pathway - Zhaoping Wang; Xiangyu Chen; Jingxing Liu; Yingcui Wang; Suhua Zhang (Taylor & Francis Group, 2022)
Proprotein convertase subtilisin kexin type 9 (PCSK9) is a well-known proprotein convertase that influences foam cell formation and modulates atherosclerosis. Inclisiran is a novel chemosynthetic small interfering RNA that inhibits PCSK9 synthesis. This study aimed to explore the effect of inclisiran on oxidized low-density lipoprotein (ox-LDL)-induced foam cell formation in Raw264.7 macrophages and to investigate the underlying mechanisms. Raw264.7 cells were treated with ox-LDL to induce the formation of macrophage-derived foam cells. Oil Red O staining and high-performance liquid chromatography were performed to detect lipid accumulation and cholesterol levels. Dil-ox-LDL uptake assay, CCK-8, RT-qPCR, and Western blotting analysis were performed to examine ox-LDL uptake, cell viability, and expression of scavenger receptor-related factors. Inclisiran reduced lipid accumulation in ox-LDL-treated macrophages in a dose-dependent manner. Inclisiran significantly inhibited the levels of total cholesterol, free cholesterol, and cholesterol ester in the supernatant of Raw264.7 cells. Inclisiran reduced ox-LDL uptake and increased Raw264.7 cell viability. Meanwhile, inclisiran downregulated the expression of SR-A, LOX-1, and CD36 and upregulated SR-BI, ApoE, and ABCA1. Furthermore, inclisiran increased PPARγ activity and decreased NF-κB activity. An inhibitor of PPARγ (T0070907) reversed the beneficial effects of inclisiran on ox-LDL uptake, NF-κB inactivation, and cytokine expression. In conclusion, these data suggested that inclisiran inhibited the formation of macrophage-derived foam cells by activating the PPARγ pathway.Highlights Inclisiran reduces lipid accumulation in Raw264.7 cells; Inclisiran reduces ox-LDL uptake and increases Raw264.7 cell viability; Inclisiran inhibits foam cell formation by activating the PPARγ pathway.